Sexuality and HIV prevention: consensus and dissent of Catholic youths - Pablo Luiz Santos Couto (Universidad de Antioquia, 2018)
Objective. To analyze the consensus and dissent of Catholics youths about HIV/AIDS prevention from their representations about sexuality.